MATHEMATICAL MODELING OF JOINT ECONOMIC ACTIVITY OF PEOPLE - Shiyan, Anatoliy (Scientific Works of Vinnytsia National Technical University, 2015)
Mathematical apparatus intended for modeling of joint economic behaviour and classification of relations between the types of economic behaviour of people has been elaborated.